The Economics of Energy Obtained from Biomass and Second Generation Biofuels - Beneš, Ondřej (2020)
The thesis builds on the dataset, originally put together by Novotný (2019), prolonging it and adding sever new titles. A technological and legislation overview are provided in the first part of the thesis, providing overall context. We look at all 2nd generation (2G) end products, the three major conversion pathways and especially the feedstock, with differentiates 2G biofuels from the conventional, 1G fuels. In the legislation review a timeline pointing out the major changes and policies, as well as brief comments on their applications, is built for the three top players in biofuels production, the U.S., Brazil, and the European Union. Because the 1st generation is strongly associated with the food-fuel debate we then focus on its link to the 2G as well, showing how these links are weaker and manageable, although with some challenges still present. We also look at other environmental and social dilemmas, such as emission life-cycle assessment, the water footprint, or “political lock-in” risks. In the final section price targets, ensuring market penetration, are posed for 2G fuels based on the data collected for 1G fuels and fossil fuels, plus their respective feedstocks. Also, Pearson correlation matrices are used to illustrate the weak connection between groups of fuels (1G, 2G, fossil) and various stock groups. Finally, we look at the volatile profitability of biofuel stocks.